Baleen wear reveals intraoral water flow patterns of mysticete filter feeding. (29th January 2016) - Werth, Alexander J.; Straley, Janice M.; Shadwick, Robert E.
ABSTRACT: A survey of macroscopic and microscopic wear patterns in the baleen of eight whale species (Cetacea: Mysticeti) discloses structural, functional, and life history properties of this neomorphic keratinous tissue, including evidence of intraoral water flow patterns involved in filter feeding. All baleen demonstrates wear, particularly on its medial and ventral edges, as flat outer layers of cortical keratin erode to reveal horn tubes, also of keratin, which emerge as hair‐like fringes. This study quantified five additional categories of specific wear: pitting of plates, scratching of plates, scuffing of fringes, shortening of fringes, and reorientation of fringes (including fringes directed between plates to the exterior of the mouth). Blue whale baleen showed the most pitting and sei whale baleen the most scratching; gray whale baleen had the most fringe wear. The location of worn baleen within the mouth suggests that direct contact with the tongue is not responsible for most wear, and that flowing water as well as abrasive prey or sediment carried by the flowing water likely causes pitting and scratching of plates as well as fringe fraying, scuffing, shortening, and reorientation. Baleen also has elevated vertical and horizontal ridges that are unrelated to wear; these are probably related to growth and may allow for age determination. J. Morphol. 277:453–471, 2016. © 2016 Wiley Periodicals, Inc.